PENGARUH GAYA KEPEMIMPINAN, REWARD, DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA USAHA FOTOCOPY HASBONA SURAKARTA - Paramita Dewi Manggiasih; Lamidi Lamidi; Sutarno Sutarno (Universitas Slamet Riyadi, 2020)
This reasearch was conduted at Hasbona Photocopy business in Surakarta, the type of data used is qualitative data and quantitative data. The population in this study were all employees in Hasbona Photocopy business in Surakarta, amounting to 70 people. The sampling tecnique in this study used nonprobability sample saturated sample of 70 respondents. The analysis tecnique uses multiple linear regression analysis. The result of this study stated leadership style, reward, and punishment have a significant effect on the performance of employee Hasbona photocopy business in Surakarta.